(untitled) (Journal of Scientific Research, 2022)
A microstrip patch antenna is considered the most suitable radiating and receiving element for millimeter-wave application due to its low cost, simple construction, low weight, and ease with which it is integrated into the circuits. In this paper, we have reported the effects of different symmetric shaped slots on millimeter-wave patch antenna design and its performance at 10 GHz frequency in the X band (8-12 GHZ). The rectangular, circular, and elliptical slots area is kept constant at 11.2 mm2. The radius of circular and spherical slots is the same. High-frequency simulation software (HFSS) simulation results in parameters like S11 (reflection coefficient), Y-parameter (driving point admittance), Radiation Pattern, 3D Polar plot and illustrate that the results are in good agreement with the desired value. A rectangular slot is found to achieve the target resonance frequency with a low voltage standing wave ratio (VSWR) towards a ‘good match.’ Circular, spherical, and elliptical-shaped slots have high VSWR values, indicating a larger degree of mismatch. Surprisingly, results are obtained for the spherical-shaped slot, implying that the antenna will work at the target resonance frequency and has a Dual-Resonance. The proposed antenna design is suitable for 5G device applications in the X band.